Outcomes within 100 days of hematopoietic cell transplantation in pediatric patients: insights from an intensive care unit in Colombia - Lasso-Palomino, Rubén E.; Medina, Diego; Franco, Alexis Antonio; Soto-Aparicio, María José; Manzi Tarapues, Eliana; Muñoz, Diana Marcela; Salazar, Edgar; López, Jhon; Devia, Angela; Martínez-Betancur, Sofía; Sierra, Jimena; Arias, Anita V.; et al. (Frontiers in Pediatrics, 2024)
Hematopoietic cell transplantation (HCT) has become an essential therapeutic modality for pediatric patients with malignant and non-malignant conditions. Despite its effectiveness, many patients experience post-transplant complications often leading into life-threatening conditions requiring specialized care in a Pediatric Intensive Care Unit (PICU). This study aims to describe clinical characteristics associated with mortality in pediatric HCT patients who needed PICU care within 100 days post-transplant in a resource-limited country. A retrospective cohort study was conducted involving pediatric HCT patients (<18 years old) admitted to our PICU from January 2012 to December 2021. Variables were characterized according to their nature, employing appropriate measures of central tendency and dispersion. The relationship between mortality and patient clinical characteristics was assessed using the Chi-square test or the Mann-Whitney U test, as applicable. A p-value of < 0.05 was considered statistically significant. A Kaplan Meier survival curve was performed considering the days from HCT to death during PICU admission and a Cox regression analysis was conducted to analyze the association between PRISM III score and risk of death. Data analysis was executed utilizing the STATA SE v18 statistical software package. Of 316 HCTs, 69 patients required admission to the PICU. Haploidentical transplants from related donors were performed in 72.5% of these patients. The primary cause of PICU admission was infection, accounting for 68.1% (n=47) of cases. Factors significantly associated with mortality included a PRISM III score > 20 (p 0.002), mechanical ventilation (p 0.007) , renal replacement therapy (p 0.002) and vasoactive support (p=<0.001). A total of 27 patients succumbed during their PICU stay. Kaplan Meier curve showed a survival rate of 51.6% at100-days post-transplant. A PRISM III score higher than 20 points was related with mortality (Hazard ratio 5.71 CI 95% 2.09-15.5). This study examines critical factors associated with mortality in pediatric HCT recipients who required admission to our PICU within the first 100 days post-transplant. Our findings indicate that infectious complications, alongside the need for advanced cardiovascular, respiratory, and renal support are strongly correlated with mortality. These results underscore the importance of early risk factor identification and targeted interventions to optimize patient outcomes.